Controlling the triboelectric properties and tribological behavior of polyimide materials via plasma treatment. (November 2022) - Sun, Xiao; Liu, Yongjian; Luo, Ning; Liu, Ying; Feng, Yange; Chen, Shougang; Wang, Daoai
Abstract: Surface charge density greatly influences triboelectric properties and tribological behavior. Given the limitations of current techniques for regulating surface charge, a novel plasma-irradiation-based surface treatment was used to enhance the triboelectric properties and optimize the tribological behavior of polyimide (PI) films. An in-situ two-step Ar+O2 reactive ion etching (RIE) plasma treatment was used to etch the surface of the PI films to enhance the triboelectric performance of PI-PA11-based triboelectric nanogenerators (TENGs). The generation of granular nanostructures on the PI film surface enhanced the effective contact area between triboelectric layers. The C-O and CO content was also greatly increased, improving the electron affinity of the PI films. At the same time, to obtain a fully antistatic PI surface in a PI-PVDF-based TENG, the optimal irradiation time was calculated. In addition, to control the tribological behavior, the surface charge of PI film was successfully eliminated by a one-step Ar plasma irradiation, and the regulation of the coefficient of friction was realized, which significantly improved the friction stability and wear resistance of the material. This new approach can find wide applications in energy harvesting, industrial production, electronic circuit, and other applications. Graphical Abstract: ga1 Highlights: The effective regulation of surface morphology and surface chemical structure has been realized. Triboelectric properties can be controlled by two-step Ar+O2 plasma irradiation and realize energy harvesting or antistatic. Tribological behaviors can be controlled by one-step Ar plasma irradiation, which can regulate coefficient of friction . The regulation mechanism on triboelectric properties and tribological behaviors of PI films has been investigated.